High-Frequency Direct Organogenesis of Sugarcane (Saccharum officinarum L.) varieties of Bangladesh (Plant Tissue Culture and Biotechnology, 2026)
An efficient and reproducible in vitro regeneration protocol was developed for sugarcane varieties, Isd 33, Isd 37 and Isd 40 using five-month-old leaf sheath explants with direct shoot regeneration on MS medium supplemented with NAA. In this study, the highest shoot regeneration in Isd 33 and Isd 40 was obtained on MS medium supplemented with 10.0 mg/l NAA, producing 29.17 and 33.33 shoots per explant with 90 and 93.3% response, respectively. In Isd 37, maximum shoot induction was observed at 9.0 mg/l NAA with 25.49 shoots per explant and 90% response. Successful shoot regeneration was achieved within 65 days of culture. Rooting was observed subsequently, where in Isd 33, 100% rooting produced 33.83  roots per shoot with root length of 5.08  cm at 2.5 mg/l NAA, with root initiation occurring within 3 to 7 days, while in Isd 37, 100% rooting produced 31.83  roots per shoot with root length of 5.40  cm at 2.5 mg/l NAA, and in Isd 40, 100% rooting produced 28.33 roots per shoot with root length of 6.12 cm at 2.0 mg/l NAA, with full root development completed within 40 days of transfer to rooting medium. Plantlets that were acclimatized displayed 100% survival in Isd 33 and Isd 37 and 88.89% survival in Isd 40. Overall, this direct NAA-dependent protocol supported efficient shoot regeneration, rooting and acclimatization in all three varieties, with variety-specific optimal NAA concentrations indicating that regeneration response in sugarcane is genotype-dependent rather than attributable to a single superior variety.Plant Tissue Cult. & Biotech. 36(1): 165-175, 2026 (June)